2020
DOI: 10.1136/jitc-2019-000336
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic associations of T cell cancer immune response-related genes with T cell phenotypes and clinical outcomes of early-stage lung cancer

Abstract: BackgroundRecent advances in T cell-related immunotherapy have brought remarkable progress in the treatment of non-small cell lung cancer (NSCLC). However, whether and how genetic variations of T cell cancer immune response genes can influence clinical outcomes of NSCLC patients remain obscure.MethodsIn this multiphase study, we assessed 2450 single-nucleotide polymorphisms (SNPs) from 280 T cell cancer immune response-related genes in 941 early-stage NSCLC patients (discovery n=536; validation n=405) to analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Interestingly, in analyses stratified by stage, we found a greater number of significant associations between PRSs for cancers and immune traits than in overall association analyses. Previous studies have focused mainly on predicting prognosis according to the immune landscape in the early stages, owing to sample sizes [ 43 , 44 , 45 , 46 ]. Although this study had some sample size limitations, we systematically evaluated association analyses by early and advanced stages across the four cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in analyses stratified by stage, we found a greater number of significant associations between PRSs for cancers and immune traits than in overall association analyses. Previous studies have focused mainly on predicting prognosis according to the immune landscape in the early stages, owing to sample sizes [ 43 , 44 , 45 , 46 ]. Although this study had some sample size limitations, we systematically evaluated association analyses by early and advanced stages across the four cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…PD-1/PD-L1 polymorphisms were associated with overall cancer susceptibility ( 47 ) and a prognostic impact ( 48 ). Although less studied, polymorphisms in IDO1 have been reported to be associated with overall survival in early stage cancer ( 49 , 50 ). In a cohort of healthy individuals, a polymorphism in the promoter region of IDO1 was associated with altered serum Trp concentrations ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study in south India reported that patients with the PDCD1LG2 SNP rs7854413 and lymphatic filariasis infection were susceptible to chronic lymphatic pathologies (40), and rs7854413 polymorphism was related to advanced fibrosis and development of hepatocellular carcinoma from patient with non-alcoholic steatohepatitis (41). Notably, rs7854413 was also associated with recurrence in patients with early-stage NSCLC (42). During the process of literature review, no studies on these PDCD1LG2 SNPs other than rs7854413 were reported.…”
Section: Discussionmentioning
confidence: 99%